Design and performance evaluation of an integrated solar dryer for fish and marine products through computational fluid dynamics simulation - Tan, Adeline Shu Ting (2023)
There are several drawbacks remain to be resolved for the application of solar dryer in fish drying, such include low solar intensity, uniformity of heat distribution, and inadequate air circulation. In this present study, a mixed mode type solar dryer namely, Integrated Solar Dryer (INSOLER) was presented and the performance under pseudo natural convection was studied through Computational Fluid Dynamics (CFD) simulation under inlet mass flow rate of 0.012 kg/s and solar irradiance of 438.58 W/m2. In this solar dryer, enhancement was proposed on the design of solar heat collector, air distribution system, and chimney, which governs the temperature, uniformity, and air circulation, respectively, to address the limitation mentioned. The main purpose of this research is to address the gaps in the design of these components and identify the improvements in term of heat transfer and fluid flow characteristics. The first objective of this work aimed to determine the performance of baffle-type solar heat collector (B-SHC) with different baffle arrangement, namely longitudinal SHC (L-SHC) and transversal SHC (T-SHC). It was found that L-SHC offers higher outlet temperature, collector efficiency, and thermo-hydraulic performance factor (THPF) of 59.43 °C, 46.2% and 2.1, respectively, indicating flow resistant presence in the air passage of longitudinal arrangement does not outweigh the enhancement of heat transfer in the collector. To ensure uniform heat distribution across the drying house, air distribution system with different perforation direction – upward and downward, was proposed. The latter configuration was proposed to address potential faulty operation caused by moisture accumulation and to ensure maximum heat transfer enhancement in the solar dryer. As expected, this perforation demonstrated more uniform temperature profile with p-value greater than 0.01 across different tray level and exhibits superior performance with heat transfer enhancement factor of 1.09. Followed by, three different chimney placement – exterior chimney, interior chimney, and interior chimney with perforation, were evaluated in term of the temperature distribution and the velocity profile attained across the drying house. Interior chimney was proposed to prevent continuous outflow of air which ultimately promotes heat accumulation in the dryer. Interior chimney with perforation demonstrated highest temperature with a value of 67 °C and the velocity profile obtained implied extended air residence time in the solar dryer due to the presence of greater air resistance. Lastly, INSOLER developed with the combination of these improvements offers drying temperature range suitable for the drying of fish (maximum temperature = 66 °C), uniform temperature profile across different tray level (p-value>0.01), and air circulation that promote heat accumulation in the drying area, which compensated the limitations of solar dryer mentioned earlier. For optimization purpose, the performance of INSOLER under different mass flow rate and solar irradiance was also studied. It was revealed that there is a difficulty in compromising between attaining allowable temperature range and better uniformity. With these findings obtained, this research could serve as a baseline study for the implementation of solar heat collector, air distribution, and chimney design covered in this work as a continuous effort for solar dryer enhancement to achieve sustainable development in food processing industry.